2020
DOI: 10.1055/s-0041-1726136
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Nausea and Vomiting (CINV) with GI Cancer Chemotherapy: Do We Need CINV Risk Score Over and Above Antiemetic Guidelines in Prescribing Antiemetic Regime?

Abstract: Background Various predictive models have been developed which incorporates patient risk factors into the selection of optimal antiemetic therapy, one of which is chemotherapy-induced nausea and vomiting (CINV) risk scoring system developed by Multinational Association of Supportive Care in Cancer (MASCC). Patients and Methods Consecutive patients with gastrointestinal malignancy who had not received previous chemotherapy were eligible for enrollment in the study if they were scheduled to receive at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In this phase II randomised multicentre study, we found that nausea was unpredictable, whether the antiemetic was adjusted or not. A clear majority (86%) of the studied patients experienced some CINV despite the usage of the recommended combination of antiemetics, in accordance with international guidelines (30,31). The hypothesis was that no difference in nausea would be found between standard antiemetic treatment and adjusted antiemetic treatment based on genetic biomarkers (SNPs).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this phase II randomised multicentre study, we found that nausea was unpredictable, whether the antiemetic was adjusted or not. A clear majority (86%) of the studied patients experienced some CINV despite the usage of the recommended combination of antiemetics, in accordance with international guidelines (30,31). The hypothesis was that no difference in nausea would be found between standard antiemetic treatment and adjusted antiemetic treatment based on genetic biomarkers (SNPs).…”
Section: Discussionmentioning
confidence: 74%
“…Otherwise, it is known that CINV can occur regardless of the antiemetic that the patient receives (34,35). It is known that CINV is a complicated symptom that needs to be addressed both medically and non-medically for better results (30,36). The physiological causes of nausea are challenging to understand in BC patients, though it is known that some cytostatic medications harm cells in the intestinal wall (31,37).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, clinical studies have shown significant breakthrough CINV rates with the use of these prophylactic regimens despite guideline-mandated use. 8 This has led to trials evaluating the role of adding a prophylactic NK-1RA to all moderately emetogenic regimens. 9 Olanzapine is an atypical antipsychotic agent that blocks multiple neurotransmitters, including dopamine, serotonin, catecholamines, histamine, and acetylcholine, in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors are associated with the development of CINV and can be categorized into two main groups: chemotherapy-related and patient-related risk factors (D'Souza et al, 2020). The proper assessment of the emetogenic potential of the drugs combined with the individual risk factors is essential to evaluate an appropriate CINV prophylaxis (Dranitsaris et al, 2016).…”
Section: Wwwjpadrcom M Introductionmentioning
confidence: 99%